CYTOTOPOGRAPHIC FEATURES OF PLASMA CELLS IN THE MAJOR SALIVARY GLANDS OF RATS IN NORM AND AT DIFFERENT FUNCTIONAL STATES - Yashchenko, A.M.; Yeroshenko, H.A.; Koptev, M.M.; Shevchenko, K.V. (World of Medicine and Biology, 2017)
The aim of the study was to determine the cytotopographic features of plasma cells in the major salivary glands of rats in norm and in functional states caused by proserin and platyphylline. The study was carried out on 100 white Wistar male rats with body weight (185 ± 20) g. The first experimental group consisted of 40 animals which received platyphylline (cholinolytic) at a dose of 0.3 mg / kg body weight; the second experimental group included 40 animals with proserin introduction (anticholinesterase drug) at a dose of 0.1 mg / kg body weight; the control group included 20 similar intact animals. The animals were euthanized with an overdose of thiopental anesthesia. Platyphylline and proserin effect leads to the increase in the plasmocytes number of the major salivary glands of rats, which is a morphological confirmation of the local protective barrier enhancement in response to stimulation. Stimulation with platyphylline especially leads to the increase in the number of plasmocytes in the periductal connective tissue of the submandibular gland. Proserin causes the increase in the number of plasmocytes in submandibular and sublingual glands predominantly in periacinar interstitium, and in the parotid glands − in periductal stroma.
Keywords: salivary glands; plasmocytes; platyphylline; proserin